2021
DOI: 10.3233/jad-210269
|View full text |Cite
|
Sign up to set email alerts
|

A Modified CAIDE Risk Score as a Screening Tool for Cognitive Impairment in Older Adults

Abstract: Background: Although an efficacious dementia-risk score system, Cardiovascular Risk Factors, Aging, and Dementia (CAIDE) was derived using midlife risk factors in a population with low educational attainment that does not reflect today’s US population, and requires laboratory biomarkers, which are not always available. Objective: Develop and validate a modified CAIDE (mCAIDE) system and test its ability to predict presence, severity, and etiology of cognitive impairment in older adults. Methods: Population con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
0
18
1
Order By: Relevance
“…The Cardiovascular Risk Factors, Aging and Dementia (CAIDE), a midlife composite vascular risk score that does not require labs and better reflects the age and education distribution of the study population, was associated with greater cognitive decline [256] and found to predict dementia risk 20 years [257] and even 40 years later [258]. In addition, a higher CAIDE risk score was linked to lower performance on global and domain-specific cognitive tests and helped discriminate cognitive impairment from normal cognition, MCI and dementia cases, and particularly VCI cases from controls [259]. Other vascular risk scores such as the NOMAS GVRS (Global Vascular Risk Score) were found to be inversely associated with level of global cognition and shown to better predict declines in processing speed and memory compared to CAIDE, likely because of an additional inclusion of smoking and glucose levels [260], further supporting the idea that a higher number of vascular risk factors within an individual better predicts cognitive decline.…”
Section: The Impact Of Combinations Of Risk Factors On Vcimentioning
confidence: 91%
“…The Cardiovascular Risk Factors, Aging and Dementia (CAIDE), a midlife composite vascular risk score that does not require labs and better reflects the age and education distribution of the study population, was associated with greater cognitive decline [256] and found to predict dementia risk 20 years [257] and even 40 years later [258]. In addition, a higher CAIDE risk score was linked to lower performance on global and domain-specific cognitive tests and helped discriminate cognitive impairment from normal cognition, MCI and dementia cases, and particularly VCI cases from controls [259]. Other vascular risk scores such as the NOMAS GVRS (Global Vascular Risk Score) were found to be inversely associated with level of global cognition and shown to better predict declines in processing speed and memory compared to CAIDE, likely because of an additional inclusion of smoking and glucose levels [260], further supporting the idea that a higher number of vascular risk factors within an individual better predicts cognitive decline.…”
Section: The Impact Of Combinations Of Risk Factors On Vcimentioning
confidence: 91%
“…The CAIDE and mCAIDE risk scores for each participant were calculated using the published equations using the following variables: age, sex, hypertension, obesity, and hypercholesteremia, (Supplementary Tables 1 & 2) [8,13]. Physical activity assessments were unavailable; however, CAIDE remains predictive of dementia when physical activity is not included [27].…”
Section: Methodsmentioning
confidence: 99%
“…However, the prognostic utility of CAIDE in other populations has been more limited [9,11,12]. As such, CAIDE has recently been recalibrated using a multi-ethnic cohort of community-dwelling older adults in the US to predict late-life dementia that reweights age and education to account for the older age group and higher educational attainment compared to the original development population [13]. The modified CAIDE (mCAIDE) demonstrated good discriminative performance between controls and all-cause dementia (AUC = 0.8) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced practice nurses and neurologists will complete a comprehensive physical and neurological examination of each participant (33, 34). This examination will include assessments of vital signs in a sitting and standing position, mental status, cranial nerve, reflexes, sensation, balance, coordination, and motor skills and includes the Unified Parkison’s Disease Rating Scale – Part III Motor Examination (35), modified Hoehn and Yahr staging (36), Lewy Body Composite Risk Score (37), modified Hachinski Ischemic Scale (38), and modified CAIDE scale (39).…”
Section: Methodsmentioning
confidence: 99%